Polarity Dependence of Transport of Pharmaceuticals and Personal Care Products Through Birnessite-Coated Porous Media - Li, Ye; Zhuang, Jie; Essington, Michael E.; Chen, Xijuan (Frontiers in Environmental Science, 2021)
Pharmaceuticals and personal care products (PPCPs) have drawn increasing concern of environmental health as they are continuously released into the environment. This study examined the effects of birnessite (δ-MnO2) on the transport and retention of five PPCPs in porous media under steady saturated flow conditions. Considering natural birnessite occurs as discrete particles and small nodules, birnessite-coated sand was used to mimic natural regime of birnessite in the environment. Batch isotherm experiments were conducted using uncoated and birnessite-coated sand, results showed that the difference in the affinity of the five PPCPs was correlated to their polarity characteristics. Column experiments were conducted by mixing 0%, 10% and 20% birnessite-coated sands with the uncoated sands. These three percentages are equivalent to three contents of manganese (Mn) in the experimental columns (0, 55, and 109 μg Mn g-1 sand). Results suggested that polar compounds (such as bisphenol-A, tetracycline, and ciprofloxacin) had higher affinity to birnessite-coated sands than the weak polar compounds (such as ibuprofen and carbamazepine) because the polarity was favorable to electrostatic attraction and oxidative reaction. Overall, birnessite decreased the mobility of polar PPCPs, but exerted no significant effect on the mobility of weak polar PPCPs under continuous flow conditions. The polarity-based correlation extended traditional electrostatic theory while well interpreting the complicated effects of birnessite on the adsorption and transport of PPCPs, especially neutral or non-dissociated compounds like carbamazepine.